MK3: On optimizing the management of cascades or systems of reservoirs at catchment level - Meynell, Peter-John; Carew-Reid, Jeremy; Ward, Peter; Sawdon, John; Ketelsen, Tarek (2010)
This project is about scaling up to the catchment level the results obtained from optimizing the management of individual reservoirs. As such, it draws on results from MKs 1 and 2. It seeks to understand at the catchment scale the cumulative upstream and downstream consequences of management decisions taken for multiple reservoirs. It includes the study of land degradation and reservoir siltation processes.